Pengaruh Model Project Based Learning (PjBL) dalam Menulis Teks Eksposisi pada Siswa Kelas VIII SMPN 15 Kota Jambi - Sitohang, Rinawati; Harahap, Eddy Pahar; Purba, Andiopenta (Jurnal Ilmiah Dikdaya, 2023)
This study aims to test and find out whether or not there is an influence of the Project Based Learning (PjBL) model in writing exposition texts in class VIII students of SMPN 15 Jambi City. The data in this study were collected by observation, interviews and tests. This type of research is a pre-experimental design research in the form of a one group research group pre-test post-test design. The form of the method used in this study is a quantitative approach. Before the data is analyzed, the normality and homogeneity of the data are tested first as a prerequisite test. Testing the normality of the data using the Shapiro-Wilks using the SPSS 26 application program. The data homogeneity test was carried out using the Levene Statistic formula in the SPSS 26 program with a sig value > 0.05. The t test for pretest and posttest data also used SPSS 26. Based on the results of the data normality test using the SPSS 26 application program, a significance value of > 0.05 was obtained, so we can conclude that the data is normally distributed. Then on the homogeneity test results obtained a significance value of 0.91> 0.05, then the data is homogeneous. Based on the results of the t test on pretest and posttest data, it is less than 0.05. It is known that the Sig. (2.tailed) of 0.000 <0.05, it can be concluded that there is a difference between the results of the students' ability to write exposition texts at the pretest and posttest stages. If seen based on the N-gain test, it can be concluded that there is a difference between the pretest and posttest values where the pretest value is 55 and the posttest is 81 with an average value of 0.60 which is included in the medium category. based on the results of data analysis, the Project Based Learning (PjBL) learning model has an effect on learning to write exposition texts